Diabetic foot complicated by vertebral osteomyelitis and epidural abscess. (18th May 2016) - Mantovani, Alessandro; Trombetta, Maddalena; Imbriaco, Chiara; Rigolon, Riccardo; Mingolla, Lucia; Zamboni, Federica; Dal Molin, Francesca; Cioccoloni, Dario; Sanga, Viola; Bruti, Massimiliano; Brocco, Enrico; Conti, Michela; et al.
Summary: Vertebral osteomyelitis (or spondylodiscitis) is steadily increasing in Western countries and often results from hematogenous seeding, direct inoculation during spinal surgery, or contiguous spread from an infection in the adjacent soft tissue. We present the case of a 67-year-old white patient with type 2 diabetes who went to Hospital for high fever, back pain, and worsening of known infected ulcers in the left foot. Despite intravenous antibiotic treatment and surgical debridement of the foot infection, high fever and lower back pain continued. Bone biopsy and two consecutive blood cultures were positive for Staphylococcus aureus . A spinal magnetic resonance imaging (MRI) was performed, revealing serious osteomyelitis in L4 and L5 complicated by an epidural abscess. Contiguous or other distant focuses of infection were not identified. In this case, diabetic foot could be considered as a primary distant focus for vertebral osteomyelitis. Clinicians should consider vertebral osteomyelitis as a 'possible' diagnosis in patients with type 2 diabetes complicated by foot infection that is associated with fever and lower back pain. Learning points: Vertebral osteomyelitis is increasing in Western countries, especially in patients with type 2 diabetes. The primary focus of infection is the genitourinary tract followed by skin, soft tissue, endocarditis, bursitis, septic arthritis, and intravascular access. Diabetic foot could be a rare primary focus of infection for vertebral osteomyelitis, and, however, vertebral osteomyelitis could be a serious, albeit rare, complication of diabetic foot. Clinicians should keep in mind the many potential complications of diabetic foot ulcerations and consider vertebral osteomyelitis as a "possible" diagnosis in patients with type 2 diabetes and foot ulcers associated with nonspecific symptoms such as lower back pain. Early diagnosis and correct management of vertebral osteomyelitis are crucial to improve clinical outcomes.